Analysis f design and technology features of industrial shredders - Fyk, Sviatoslav; Stupnytskyy, Vadym (Видавництво Львівської політехніки, 2024)
The article is devoted to an overview of shredder designs for the processing industry and domestic and industrial waste utilization. The shredder designs of leading European companies are presented. Their design and technological advantages and disadvantages are analyzed. Recommendations for improving the design of knives for shredding various types of waste – from construction to household waste – are added. The advantages of modern shredder designs manufactured by the Kivshservice company (Ukraine) are shown.
Keywords: shredder; industrial waste; waste utilization; shredding knives; shredder design